Penerapan Media Mahkota Jaringan Makanan Berbasis Gambar untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPA - Sari, Meirita; Anggraini, Atika; Hikmah, Nur; Suwarni (CV. Cendekiawan Muda Sriwijaya, 2024)
This research aims to analyze the effectiveness of implementing the Mahkota Jaringan Makanan (Food Web Crown) visual-based media in enhancing students' understanding of science, particularly the concept of food webs. The study employs a descriptive qualitative approach. The subjects are 29 seventh-grade students from SMPN 25, selected through purposive sampling. Research instruments include conceptual understanding tests, observation sheets, interviews, and questionnaires to measure changes in students' comprehension and engagement during the learning process. The results indicate a significant improvement in the students' average scores after applying the media, with an average learning outcome increase of 41.5%. Additionally, the media fostered active student participation during the learning activities, making them more enthusiastic and capable of collaborating with their classmates. The image-based Mahkota provided strong visual support, helping students understand the relationships between food web components more concretely and interactively. The use of this media also helped reduce misconceptions about the roles of producers, consumers, and decomposers in ecosystems. Thus, this media can be an innovative and enjoyable alternative teaching method, which can be integrated into the science curriculum to enhance learning quality.